Role of hydroxyl production and heat release in the two-zone fuel-rich adiabatic dimethyl ether/air flames at atmospheric pressure - Shvartsberg, V.M.; Bunev, V.A.; Bolshova, T.A.; Babkin, V.S. (Combustion theory and modelling, 2017)
Fuel-rich laminar adiabatic flames of premixed dimethyl ether/air mixtures at a high initial temperature and atmospheric pressure have been studied by numerical simulation and sensitivity analysis. These flames, having two heat release zones, are of great interest as an unusual and little-studied subject. We have investigated the chemical processes occurring in the two zones and analysed the mechanism of heat release in the flame. It has been found that the key reactions that have a significant influence on the flame speed are those involving dimethyl ether and the products of its incomplete oxidation. Calculation of the heat release rate confirms the presence of two heat release zones in the flame. A comparison of the reactions making a major contribution to the heat release with those significantly affecting the flame speed indicates that the main factor determining the flame speed is the formation of hydroxyls, rather than heat release. Analysis of the flame speed sensitivity shows that in the case of a two-zone structure of the flame, its speed is mainly determined by the reactions taking place in the low-temperature zone. That is, the cool zone with a higher temperature gradient is the leading one.